Edukasi Literasi Keuangan Kepada Ibu – Ibu dan Remaja Terkait Pinjaman Online serta Dampaknya - Mokhtar Sayyid; Agustinus Sahlukh; Didik Puji Wahyono; Megawati Megawati; Maria Ulfa (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service activity aims to provide financial literacy education on online loans to the community of made villages, especially mothers and adolescents. The large number of online loan offers to this group results in knowledge of the characteristics and requirements of these online loans need to be well understood. The implementation method of this community service activity is carried out through the preliminary stage, implementation stage and monitoring stage. This Community Service activity concluded that financial literacy education, especially related to online loans, is very useful for mothers and adolescents, because there are still many who do not understand basic accounting and basic finance. The group still does not consider the inherent risks of the ease of obtaining online loans